Sleep Spindle Abnormalities with Generalized Spike-Wave Discharges - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
Sleep and sleep spindle parameters were examined in 15 children with primary generalized spike-and-wave discharges at University Hospitals, Leuven, Belgium.